Oblicza dehumanizacji dydaktyki = Faces of didactics dehumanization - Sajdak-Burska, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article analyses the situation of didactics using the "dehumanization" category. It considers the issue of teacher education and the dehumanising mechanisms associated with the mechanistic implementation of educational standards and the atheoretical nature of education. The author focuses on the difficulty of combining humanistic concepts of teacher education with the implementation of teacher education standards. The author also presents the problem of dehumanisation of didactics due to its popular understanding and denial of its status as a scientific discipline.
Keywords: dydaktyka; dehumanizacja; kształcenie nauczycieli; nowoczesne technologie; didactics; dehumanisation; teacher education; modern technologies